Utilization of ionic liquids as solvents and co-catalysts in the production of cyclic carbonates from CO2 - Ventura, Alexandre Lopes do Rosário (2019)
The production of useful compounds through the chemical fixation of CO2 has attracted increasing interest from the scientific community, due to its abundance in nature, non-toxicity and low-cost. One of the most promising applications is the direct coupling of CO2 to epoxides for the production of cyclic carbonates, which holds industrial interest, due to wide range of applications namely as green solvents, electrolytes for lithium batteries and monomers for polymers production. One technical barrier that needs to be addressed for wide industrial implementation, is the separation and reutilization of catalysts, usually homogeneous Lewis acidic metal-based complexes, combined with a nucleophile. The aim of this thesis was to investigate the utilization of different ionic liquids and deep eutectic solvents, potentially able to work both as reaction solvent and as co-catalyst, as well as to allow the product separation from the reaction mixture. In this context, reaction conditions were optimized, catalyst and several co-catalysts performances were studied. Different cation and anion families of ionic liquids were also investigated, as well as deep eutectic solvents. Reactions were performed in a high-pressure apparatus and final products analyzed by 1H-NMR spectroscopy. Supercritical CO2 extraction was applied to separate the product from the reaction mixture. The catalyst system was reused three times, without loss of activity. The bromide anion and its combination with the tetrabutylammonium cation has shown the best catalytic activity. However, its utilization as a solvent is not viable due to being solid at room temperature. As a solvent, methyltrioctylammonium chloride showed promising results and proved to be a good alternative to perform the reaction, since besides favouring the reaction kinetic, it retains the catalyst allowing the product to be extracted using supercritical CO2. Moreover, a tetrabutylammonium bromide (TBABr)-based deep eutectic solvent showed the best performance as solvent and co-catalyst and constitutes a good alternative for further studies.